DISTANCE RESEARCH METHODS AND DIGITAL MAPPING - Fayziev Habibullo Abdullo o'g'li (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, students studying in the field of "Geology, prospecting and exploration of mineral deposits" are trained to develop the skills and abilities to carry out remote mapping and geological research in Geological prospecting with the help of accurate and modern tools. and in order to increase their knowledge, the introduction of the science of "Remote research methods and digital mapping" was considered.